Selective laser melting of AlSi10Mg : effects of scan direction, part placement and inert gas flow velocity on tensile strength - Ahmad Bin Anwar (2020)
The effects of laser scan direction, part placement and inert gas flow velocity on the tensile strength of aluminium alloy, AlSi10Mg parts manufactured using Selective Laser Melting (SLM), were studied. The scan direction, either in the same or opposite direction to the gas flow was the primary factor of interest due to the possible laser-spattered powder-gas interactions leading to energy loss while scanning the powder bed. The effects of flow velocity on tensile strength had shown to be more significant than part placement. It was found that scanning against the gas flow resulted in better part quality, as quantified by a higher Ultimate Tensile Strength (UTS). This relationship was interpreted and discussed based on other observations, such as the quantity of accumulated spattered powder near the outlet, images recorded using high-speed cameras, SEM-EDS tests, etc. Hence, the results suggest a concrete modification to existing scanning strategies with respect to the inert gas flow in SLM to improve part quality.